2009
DOI: 10.1002/fam.1009
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of thermal conductivity of gypsum plasterboards at ambient and elevated temperature

Abstract: SUMMARYPlasterboard often protects steel structures of buildings because it conducts heat slowly and absorbs the heat of the fire by its volumetric enthalpy. The most important property governing the heat transfer is the thermal diffusion. This property depends on the density, specific heat and thermal conductivity. The first two can be calculated based on the mass composition of the board. The thermal conductivity is more difficult to derive since it is a directional property. This paper will focus on the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
(41 reference statements)
2
11
0
1
Order By: Relevance
“…It is shown that the thermal conductivity remains stable at a lower density and then increases quickly with the increase of the density. This is in line with De Korte and Brouwers [7] and Zehner and Schlunder [8], who reported that the thermal conductivity is related not only with the density, but also strongly with the composition. It should also be pointed out that, to reach a lower thermal conductivity, it is not enough only to consider the reduction of the density.…”
Section: Thermal Physical Propertiessupporting
confidence: 90%
“…It is shown that the thermal conductivity remains stable at a lower density and then increases quickly with the increase of the density. This is in line with De Korte and Brouwers [7] and Zehner and Schlunder [8], who reported that the thermal conductivity is related not only with the density, but also strongly with the composition. It should also be pointed out that, to reach a lower thermal conductivity, it is not enough only to consider the reduction of the density.…”
Section: Thermal Physical Propertiessupporting
confidence: 90%
“…The thermal conductivity of a material is related with its density and composition, which was for instance investigated by De Korte and Brouwers [21]. However, it is shown that most of the available literature [8][9][10][11][12][13][14][15] only studied one or two types of commercially available gypsum plasterboards without providing composition information, and the effect of water content on thermal conductivity of gypsum board was not reported before.…”
Section: Thermal Properties Of Gypsummentioning
confidence: 99%
“…Based on reports of thermal conductivity for different rock types (mainly sedimentary), scholars have focused on how temperature controls thermal conductivity (Korte and Brouwers 2010; Zoth et al 1988; Seipold 1998). For example, using measurements of rock thermal conductivity in the Tarim Basin, Wang et al (1995a) determined the distribution of terrestrial heat flow, and found that the basin center had the highest heat flow, and lower heat flow in the depression area.…”
Section: Introductionmentioning
confidence: 99%